Multicomponent metal organic frameworks using amino acids and peptides : a thesis presented in partial fulfilment of the requirements of the degree of Doctor of Philosophy in Chemistry at Massey University, Manawatu, New Zealand - Dahalan, Ghadir (Massey University, 2026)
Multicomponent metal-organic frameworks (MMOFs) are a class of metal-organic frameworks (MOFs) that consist of multiple structurally unique ligands and/or metal ions/clusters. There has been an interest in flexible ligands such as amino acids and peptides. However, all studies to date have used a single type of amino acid, or peptide. I present the first multicomponent amino acids MOFs using combinations of amino acids-based ligands. In this work, we explored the development of multicomponent amino acid-based MOFs using unmodified amino acids as linkers. Despite extensive synthetic efforts, the formation of 3D MMOFs from unmodified amino acids proved unsuccessful due to the inherent structural limitations of amino acids and their preferred coordination modes with metal ions. To overcome these limitations, a new family of amino acid-derived ligands, H2XPyr (X denotes amino acids), was designed and synthesised. These linkers enable the formation of a robust framework synthesis by incorporating the amino acid functionality, which is covalently coordinated to the pyrazole group. These frameworks retain the amino acid’s chemical characteristics. Zn2XPyr frameworks are the first successful examples of multicomponent amino acid-based MOFs constructed from this new linker family. A complementary approach was pursued through the functionalisation of the MUF-77 framework, a member of the Massey University Framework (MUF) series previously developed by the Telfer Group. In this strategy, amino acids or their derivatives were installed onto the linear ditopic linkers of MUF-77, enabling precise control over the chemical microenvironment within its pores. This modular design allowed of the engineering of cooperative catalytic dyads within the pore structure, mimicking the spatial arrangement of functional residues within enzyme active sites. Two approaches were adopted for designing enzyme-inspired multicomponent MOFs: the first is incorporating amino acids into new amino acid-derived linkers capable of forming robust MMOFs, and the second is installing amino acid functionalities within well-established MOF structures (MUF-77) to create catalytically active pore environments.
Keywords: MOFs; BioMOFs; Multicomponent MOFs; Flexible MOFs; 340207 Metal organic frameworks